Negative thermal expansion in silicalite-1 and zirconium silicalite-1 having MFI structure - Bhange, Deu S.; Ramaswamy, V. (Materials Research Bulletin, 2006)
In situ high temperature X-ray diffraction (HTXRD) studies on monoclinic silicalite-1 (S-1, silica polymorph of ZSM-5) and an orthorhombic metallosilicate molecular sieve, zirconium silicalite-1 (ZrS-1) with MFI structure (Si/Zr = 50) have been carried out using a laboratory X-ray diffractometer with an Anton Parr HTK 1600 attachment. While the structure of the S-I collapsed at 1123 K forming alpha-cristobalite. S-1 and ZrS-1 showed a complex thermal expansion behavior in the temperature range 298-1023 K, ZrS-1 was stable. Powder X-ray diffraction (PXRD) data taken in this region have shown strong negative lattice thermal expansion coefficient, alpha(v) = -6.75 x 10(-6) and - 17.92 x 10(-6) K-1 in the temperature range 298-1023 K-1 for S-1 and ZrS-1 samples, respectively. The thermal expansion behavior of S-1 and ZrS-1 is anisotropic, with the relative strength of contraction along a axis is more than that along b and c axes. Three different thermal expansion regions could be identified in the overall temperature range (298-1023 K) studied, corroborating with the three steps of weight loss in the TG curve of ZrS-1 sample. While the region between 298 and 423 K, displays positive thermal expansion coefficient with alpha(v) = 2.647 x 10(-6) and 4.24 x 10(-6) K-1, the second region between 423 and 873 K shows strong negative thermal expansion (NTE) coefficient alpha(v) = -7.602 x 10(-6) and - 15.04 x 10(-6) K-1, respectively, for S-1 and ZrS-1 samples. The region between 873 and 1023 K, shows a very strong NTE coefficient with alpha(v) = - 12.08 x 10(-6) and -45.622 x 10(-6) K-1 for S-1 and ZrS-1, respectively, which is the highest in the whole temperature range studied. NTE seen over a temperature range 298-1023 K could be associated with transverse vibrations of bridging oxygen atoms in the structure which results in an apparent shortening of the Si-O distances. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; phase transitions; Thermal expansion; X-ray diffraction

NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Thermal stability of the Mobil Five type metallosilicate molecular sieves - an in situ high, temperature X-ray diffraction study - Bhange, Deu S.; Ramaswamy, Veda (Materials Research Bulletin, 2007)
We have carried out in situ high temperature X-ray diffraction (HTXRD) studies of silicalite-1 (S-1) and metallosilicate molecular sieves containing iron, titanium and zirconium having Mobil Five (MFI) structure (iron silicalite-1 (FeS-1), titanium silicalite-1 (TS-1) and zirconium silicalite-1 (ZrS-1), respectively) in order to study the thermal stability of these materials. Isomorphous substitution of Si4+ by metal atoms is confirmed by the expansion of unit cell volume by X-ray diffraction (XRD) and the presence of Si-O-M stretching band at similar to 960 cm(-1) by Fourier transform infrared (FTIR) spectroscopy. Appearance of cristobalite phase is seen at 1023 and 1173 K in S-1 and FeS-1 samples. While the samples S-1 and FeS-1 decompose completely to cristobalite at 1173 and 1323 K, respectively, the other two samples are thermally stable upto 1623 K. This transformation is irreversible. Although all materials show a negative lattice thermal expansion, their lattice thermal expansion coefficients vary. The thermal expansion behavior in all samples is anisotropic with relative strength of contraction along `a' axes is more than along `b' and V axes in S- 1, TS-1, ZrS-1 and vice versa in FeS-1. Lattice thermal expansion coefficients (alpha(v)) in the temperature range 298-1023 K were -6.75 x 10(-6) K-1 for S-1, -12.91 x 10(-6) K-1 for FeS-1, -16.02 x 10(-6) K-1 for TS-1 and -17.92 x 10(-6) K-1 for ZrS-1. The highest lattice thermal expansion coefficients (alpha(v)) obtained were -11.53 x 10(-6) K-1 for FeS-1 in temperature range 298-1173 K, -20.86 x 10(-6) K-1 for TS-1 and -25.54 x 10(-6) K-1 for ZrS-1, respectively, in the temperature range 298-1623 K. Tetravalent cation substitution for Si4+ in the lattice leads to a high thermal stability as compared to substitution by trivalent cations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; Thermal expansion; X-ray diffraction

Non-isothermal kinetic studies of the template decomposition from silicalite-1 framework-high temperature X-ray diffraction and thermogravimetric analysis - Bhange, Deu S.; Pandya, N. A.; Jha, Ratnesh Kumar; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Non-isothermal decomposition of the tetrapropylammonium cations (TPA(+)) intercalated in silicalite-1 framework has been carried out using thermogravimetric (TG) analysis and high temperature powder X-ray diffraction (HTXRD) techniques. Conversion factor for template decomposition is calculated using two methods viz., % weight loss from the thermogravimetric analysis and changes in the intensities of the Bragg reflections 101/011 and 200/020 in the HTXRD patterns scanned at different temperatures (range 298823 K). The calculated apparent activation energy for template decomposition in air was 129 and 125 kJ mol(-1), respectively, for the two techniques TG and HTXRD, calculated using the Kissinger method. By Flynn-Wall-Ozawa approach of isoconversion, apparent activation energy for template decomposition in air was 123 and 124 U mol-1, respectively, for TG and HTXRD data. The reaction order was determined using the method of Kennedy and Clark and it is similar to 2 by both the techniques. The second order of template decomposition can be attributed to the fact that TPA+ is positioned in two different orientations inside the silicalite-1 framework. Template removal occurs with a contraction in unit cell dimensions. There is a decrease in the lattice parameters of the as-synthesized silicalite-1 sample after removal of template from the framework. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: HTXRD; non-isothermal kinetics; Silicalite-1

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry

Doping-induced microstructural, textural and optical properties of In2Ti1-xVxO5+delta semiconductors and their role in the photocatalytic splitting of water - Shah, Pallavi; Bhange, Deu S.; Deshpande, Aparna; Kulkarni, Mukund S.; Gupta, Narendra M. (Materials Chemistry and Physics, 2009)
The physicochemical properties of V-doped indium titanates (In2Ti1-xVxO5-delta, 0.0 <= x <= 0.2) were investigated by using XPS, powder XRD, UV-vis, SEM and luminescence spectroscopy techniques. The Rietveld refinement of XRD data revealed that even though the V-containing samples were isostructural with In2TiO5 (orthorhombic space group Pnma), a systematic x-dependent variation was noticeable in the Ti-O bond lengths in [TiO6] octahedral units, cell parameters and in the value of delta. XPS results confirmed the coexistence of V5+ and V4+ states, leading thereby to an enhancement in oxygen non-stoichiometry in the doped samples. A loading-dependent progressive shift from 400 to 750 nm was also observed in the onset of the absorption edge, indicating a significant narrowing of the band gap. Furthermore, the samples with higher V-content were comprised of the grain clusters having larger size and an irregular shape. The UV-vis. photoluminescence and thermoluminescence studies indicate that the doping-induced lattice defects may give rise to certain closely spaced acceptor/donor energy levels in between the band gap of host matrix. The indium titanates are found to serve as stable photocatalysts for water splitting under visible light, where oxygen was the major reaction product. The role of microstructural and morphological properties in the photocatalytic activity is discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In2Ti1-xVxO5+delta photocatalysts; Luminescence spectroscopy; Microstructure; Optical properties; Structure-activity relationship; water splitting

Dynamic study of N ` N-dimethylparanitroaniline encapsulated in silicalite-1 matrix using neutron spin-echo spectroscopy - Bhange, Deu S.; Dejoie, C.; Porcher, F.; Malikova, N.; Martinetto, P.; Dooryhee, E.; Anne, M. (European Physical Journal-Special Topics, 2010)
The present work focuses on the dynamic studies of N'N-dimethyl-paranitroaniline (dmpNA) encapsulated in silicalite zeolite. Quasielastic neutron scattering (QENS) experiments are carried out using neutron spin-echo technique. Polarisation of the scattered neutron beam is measured at carefully chosen values of Q = 0.35, 0.9, 1.1 and 1.45 angstrom(-1) at fixed T = 298K and at fixed Q = 0.9 angstrom(-1) at 150, 200, 250 and 298 K. This gives insight into the motion and the related activation energy of the guest dmpNA molecule. The quasielastic signal observed in the present system within the time range considered is due to fast local rotational motions of protons of the end methyl groups. The results are in good agreement with the dynamics of methyl group rotations reported in the literature by back-scattering QENS technique.

Enhanced negative thermal expansion in MFI molecular sieves by varying framework composition - Bhange, Deu S.; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2010)
In the present investigations we have carried out the high temperature X-ray diffraction (HTXRD) studies on the metallosilicate molecular sieves iron silicalite-1 (FeS-1) samples of different Si/M ratios (Si/Fe = 50, 75, 100 and infinity) for their negative thermal expansion (NTE) behavior. All the samples exhibit NTE behavior in the temperature range 373-773 K. Systematic increase in negative thermal expansion coefficient is observed as a function of increasing Fe content in the MFI framework. Strength of the negative thermal expansion increases in the order Si/Fe = infinity < 100 < 75 < 50. It is concluded that by changing the composition of the framework of MFI, enhanced negative thermal expansion can be obtained. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: HTXRD; Negative thermal expansion; Silicalite-1

Structure, electronic structure, optical, and dehydrogenation catalytic study of (Zn1-zInz)(O1-xNx) solid solution - Mapa, Maitri; Sivaranjani, Kumarsrinivasan; Bhange, Deu S.; Saha, Biswajit; Chakraborty, Purushottam; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Chemistry of Materials, 2010)
Indium and nitrogen codoping in ZnO leads to a solid solution of InN in ZnO with I composition of(Zn1-zInz)(O1-xNx). A simple solution combustion method has been adopted to prepare the above materials in less than 10 min with metal nitrates as the metal loll source and urea as fuel. With reference to ZnO, significant increase in lattice parameters was observed with increasing In-content. However, the In2O3 phase was Observed along with InN for]it content >= 10%. Optical absorption extended into the Visible region, at least LIP to 550 nm, demonstrates an effective reduction of optical band gap due to the formation of solid Solution. A new feature observed just above O2p valence band in X-ray photoelectron spectroscopy (XPS) suggests the creation of N 2p states from InN; the N Is core level XPS result too confirms nitride contribution. Raman spectroscopy and secondary ion mass spectrometry results show direct In-N, Zn-N. and In-N-Zn fragments in (Zn1-zInz)(O1-x,N-x). Catalytic activity explored for Oxidation of 2-butanol to ethyl methyl ketone demonstrates a high selectivity at 350 and 400 degrees C. All of the above characteristics suggest the multifunctional nature of (Zn1-zInz)(O1-xNx) and its potential for other applications.

Direct synthesis of well-ordered mesoporous Al-SBA-15 and its correlation with the catalytic activity - Bhange, Pallavi; Bhange, Deu S.; Pradhan, Sivaram; Ramaswamy, Veda (Applied Catalysis A-General, 2011)
The synthesis of Al-SBA-15 under milder acidic conditions were made through an adjusting the molar H(2)O/HCl ratio which indicate the formation of Si-O-Al linkages that lead to isomorphous substitution of Si(4+) by some Al(3+) ions. By adjusting the H(2)O/HCl molar ratio, Al gets incorporated into the lattice of SBA-15, which is evidenced by XRD. N(2) adsorption, TEM, (29)Si and (27)Al MAS NMR spectroscopic data. Aluminium incorporated SBA-15 samples retained both structural and textural properties of SBA-15. The (27)Al MAS NMR confirms that a large proportion of the Al is inserted into tetrahedral positions within the framework. The Al(3+) ions could assume a tetrahedral coordination and be part of the hexagonal structure of silica in Al-SBA-15. In the present study, we have examined the effectiveness of Al-SBA-15, as an acid catalyst for the esterification of acetic acid and in benzylation of anisole. The high activity of Al-20 sample in esterification reaction has been attributed to isolated, generally tetrahedrally coordinated, framework Al species. While in benzylation of anisole, the best result was achieved with Al-5 catalyst. The selectivity for benzylanisole increases and that for dibenzylether decreases with increase in the Si/Al ratio of Al-SBA-15. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-SBA-15; Benzylation of anisole; Esterification of acetic acid

MgCl2 center dot 6PhCH(2)OH - a new molecular adduct as support material for ziegler-natta catalyst: synthesis, characterization and catalytic activity - Gnanakumar, Edwin S.; Thushara, K. S.; Bhange, Deu S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2011)
Benzyl alcohol has been used to prepare a single phase MgCl2 center dot 6BzOH molecular adduct as a support for an ethylene polymerization catalyst (Ziegler catalyst). The structural, spectroscopic and morphological aspects of the MgCl2 center dot 6BzOH molecular adduct and the Ziegler catalyst have been thoroughly studied by various physicochemical characterization techniques. The presence of MgO6 octahedrons due to the interaction of Mg2+ with six -OH groups of the benzyl alcohol is confirmed from a Raman feature at 703 cm(-1), and structural studies. The supported catalyst activity has been evaluated for the ethylene polymerization reaction. The lower polymerization activity of the titanated Ziegler-Natta catalyst compared with a standard catalyst is attributed to the strong interaction of titanium chloride with the support and associated electronic factors.

Role of doping-induced photochemical and microstructural properties in the photocatalytic activity of InVO4 for splitting of water - Rakesh, K.; Khaire, S.; Bhange, Deu S.; Dhanasekaran, P.; Deshpande, Suvarna S.; Awate, S. V.; Gupta, N. M. (Journal of Materials Science, 2011)
We report in this paper on microstructural, optical and photocatalytic properties of single-phase indium orthovanadates, as a function of doping at lattice sites. The UV-visible spectra of these samples exhibited intense UV-region bands at 250 and 350 nm, besides broad absorption band in visible region (350-700 nm). The wavelength at absorption edge and the intensity of visible absorption showed considerable increase on doping of an impurity, particularly at V or O lattice sites. Also, the samples gave rise to blue-green photoluminescence emission, with overriding bands at ca. 420, 450, 460 and 485 nm, on excitation at 240-420 nm wavelengths. The intensity of these fluorescence bands varied with excitation wavelength and impurity content of a sample. In deviation with several earlier studies, only oxygen and no hydrogen were produced during photocatalytic splitting of water, in the experiments conducted under visible light (> 395 nm) and at a pH of similar to 6.5. The O-2 yield depended on the dispersed metal co-catalyst, impurity content and the addition of methanol as sacrificial reagent. On the other hand, small quantities of hydrogen and no oxygen were evolved on UV-irradiation of pure water using metal/InVO4. These results are ascribed to flat band potentials and the doping-induced inter-band donor and acceptor charge trapping states of InVO4, the presence of which is revealed by XRD, luminescence and XPS studies. Our study also confirms that the onset of absorption edge may not necessarily correspond to band-to-band energy gap of a semiconducting material. This accounts for some anomalous band gap energies reported earlier for InVO4.

Thermal expansion properties of stannosilicate molecular sieve with MFI type structure - Niphadkar, P. S.; Bhange, Deu S.; Selvaraj, K.; Joshi, P. N. (Chemical Physics Letters, 2012)
An in situ high temperature X-ray diffraction study was carried out for investigating the thermal expansion properties of Si-MFI and SnSi-MFI molecular sieves. The thermal stability up to 973 K and a negative lattice thermal expansion in anisotropic manner was exhibited by both the phases in the temperature range of 373-973 K. The trend observed in contraction along the axes was as: a > c > b. The substitution of Sn4+ in MFI framework resulted in an expansion of unit cell volume and in an increase in the lattice thermal expansion coefficient in the temperature range 423-973 K. (C) 2012 Elsevier B. V. All rights reserved.

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction

TiO2 nanoparticles decorated on BiOCl flakes with enhanced visible light photocatalytic activity - Shinde, Deepali S.; Bhange, Pallavi D.; Jha, Ratnesh K.; Bhange, Deu S. (ChemistrySelect, 2020)
Facile preparation route for BiOCl and BiOCl/TiO2 nanocomposites with TiO2 nanoparticles decorated on BiOCl flakes via solution combustion method is reported in the present paper. Structural, textural and optical properties of the prepared materials are extensively studied using various physicochemical characterization tools such as X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), UV-vis spectroscopy (DRS), N-2 adsorption-desorption study (BET), photoluminescence spectroscopy (PL), etc. BiOCl/TiO2 nanocomposites show a red shift in the light absorption as compared to that of bare BiOCl which leads to the extended absorption in visible light region. Further photocatalytic experiments for Rhodamine B and phenol degradation demonstrate that the BiOCl/TiO2 nanocomposites have superior photocatalytic properties than bare BiOCl. Improved photocatalytic performance of BiOCl/TiO2 composites is attributed to the synergistic effect between BiOCl flakes and TiO2 nanoparticles, extended visible light absorption and delayed charge recombination.
Keywords: BiOCl; Hydoxyl radical evaluation; p-n heterojunction; phenol degradation; Photocatalysis; TiO2 nanocomposites

Preparation and structural characterization of disordered Na-gallosilicate zeolite with natrolite framework and itsK+ and NH4+ exchanged analogues exchanged analogues - Gavhane, Manjusha J.; Jha, R. K.; Nam, Kyung-Wan; Bhange, Deu S. (JOURNAL OF POROUS MATERIALS, 2024)

Synthesis and structural studies of ammonium exchanged synthetic analogue of disordered aluminosilicate natrolite - Gavhane, Manjusha J.; Jha, R. K.; Nam, Kyung-Wan; Bhange, Deu S. (Microporous and Mesoporous Materials, 2025)
The current article reports preparation and structural analysis of NH4+ exchanged form of synthetic natrolite zeolite (NH4-natrolite) with disordered structure wherein Si and Al occupies all the tetrahedral (T) sites in the zeolite framework. Structural data is used to gain insight into the structural parameters those influence thermal stability of its proposed H-form. NH4-natrolite is prepared by ion-exchange method from K-natrolite (which was also obtained by ion-exchange with Na-natrolite). Na-natrolite, K-natrolite and NH4-natrolite prepared in this study were tested for their structural, morphological and thermal analysis. Synchrotron X-ray diffraction data was utilized to estimate the crystal structures of hydrated forms of Na-natrolite, K-natrolite and NH4-exchanged natrolites. Thermal analysis of NH4-natrolite revealed that the dehydration is followed by removal of ammonia during calcination. The role of the size (radius) and nature (either divalent or monovalent) of the exchangeable cations present in the channels, the framework chemical content and extent of `T' atom ordering have been collectively discussed and correlated with the structural behaviour of calcined NH4-natrolite to explain its thermal stability in better way.
Keywords: Crystal structure of natrolite; Disordered framework; zeolite